2019
DOI: 10.14417/ap.1525
|View full text |Cite
|
Sign up to set email alerts
|

Perceções dos psicólogos portugueses acerca da aceitabilidade de uma intervenção dirigida a crianças inibidas em idade pré-escolar

Abstract: Níveis elevados e estáveis de inibição comportamental em idade pré-escolar associam-se a um risco acrescido de desenvolver perturbações de ansiedade e dificuldades com os pares. O desenvolvimento de intervenções baseadas na evidência para prevenir estas trajetórias inadaptativas têm merecido um interesse crescente. Todavia, estas intervenções ainda não se encontram disponíveis na Europa. Este estudo teve como objetivo explorar as perceções de aceitabilidade dos psicólogos portugueses acerca do componente para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This study extends prior research on the perspectives of practitioners (Guedes, Alves, et al, 2019;Guedes, Coelho, et al, 2019) and examines the perceptions of parents about the acceptability of the multicomponent Turtle Program targeted at inhibited preschoolers. Our findings support prior research, showing that the objectives and contents of PCIT (Matos et al, 2006;McCabe et al, 2005;Niec et al, 2014) and child cognitive behavioral interventions involving socioemotional learning and gradual exposure to feared situations (Gallegos-Guardado et al, 2013;Pereira et al, 2014) were perceived as acceptable by both mothers and fathers from more familyoriented cultures.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This study extends prior research on the perspectives of practitioners (Guedes, Alves, et al, 2019;Guedes, Coelho, et al, 2019) and examines the perceptions of parents about the acceptability of the multicomponent Turtle Program targeted at inhibited preschoolers. Our findings support prior research, showing that the objectives and contents of PCIT (Matos et al, 2006;McCabe et al, 2005;Niec et al, 2014) and child cognitive behavioral interventions involving socioemotional learning and gradual exposure to feared situations (Gallegos-Guardado et al, 2013;Pereira et al, 2014) were perceived as acceptable by both mothers and fathers from more familyoriented cultures.…”
Section: Discussionmentioning
confidence: 78%
“…To date, research has only focused on the perceptions of practitioners about the acceptability of the multicomponent Turtle Program (Guedes, Alves, et al, 2019;Guedes, Coelho, et al, 2019). These qualitative studies have shown that Portuguese practitioners perceived the objectives and the contents of the parent and child groups as acceptable but recommended modifications in how the intervention is presented to families, such as giving more time to families (adding more and/or follow-up sessions); broadening the focus on social interaction and emotional expressiveness; and introducing videos and interactive materials (Guedes, Alves, et al, 2019;Guedes, Coelho, et al, 2019). New qualitative studies are needed to extend prior knowledge on the perspectives of practitioners and shed light on the perceptions of parents.…”
Section: 2mentioning
confidence: 99%